Three Chalconoids and a Pterocarpene from the Roots of Tephrosia aequilata - Yoseph Atilaw (Molecules, 2017)
In our search for new antiplasmodial agents, the CH2Cl2/CH3OH (1:1) extract of the roots of Tephrosia aequilata was investigated, and observed to cause 100% mortality of the chloroquine-sensitive (3D7) strain of Plasmodium falciparum at a 10 mg/mL concentration. From this extract three new chalconoids, E-2′,6′-dimethoxy-3′,4′-(2′′,2′′-dimethyl)pyranoretrochalcone (1, aequichalcone A), Z-2′,6′-dimethoxy-3′,4′-(2′′,2′′-dimethyl)pyranoretrochalcone (2, aequichalcone B), 4′′-ethoxy-3′′-hydroxypraecansone B (3, aequichalcone C) and a new pterocarpene, 3,4:8,9-dimethylenedioxy-6a,11a-pterocarpene (4), along with seven known compounds were isolated. The purified compounds were characterized by NMR spectroscopic and mass spectrometric analyses. Compound 1 slowly converts into 2 in solution, and thus the latter may have been enriched, or formed, during the extraction and separation process. The isomeric compounds 1 and 2 were both observed in the crude extract. Some of the isolated constituents showed good to moderate antiplasmodial activity against the chloroquine-sensitive (3D7) strain of Plasmodium falciparum.